HUBUNGAN PERNIKAHAN DINI DENGAN KEJADIAN INFEKSI MENULAR SEKSUAL - Nurvy Alief Aidillah; Lianita Primi Octaviana; Nova Purmahardini (Jurnal Medicare, 2026)
Biologically, women are a population group that is susceptible to sexually transmitted infections caused by unhealthy sexual activity. Before the age of 20, women's bodies are not physically mature to carry out their reproductive functions optimally. This study aims to study the relationship between early marriage and the incidence of sexually transmitted infections in Pamekasan Regency. This study uses an analytical observational study with a cross-sectional design. The research sample amounted to 30 respondents who were selected by total sampling technique. Data analysis used the Chi-Square statistical test. Then in the distribution of STI frequencies as many as 3 cases (33.3%). The results of the statistical test obtained p value = 0.003 (p< 0.05) which means that there is a significant relationship between early marriage and STIs. The conclusion of this study is that there is a significant relationship between marriage age and the incidence of sexually transmitted infections in Pademawu District. It is hoped that the public can get better education about what risk factors can cause sexually transmitted infections, one of which is early marriage.